Capillary response to skeletal muscle contraction: evidence that redundancy between vasodilators is physiologically relevant during active hyperaemia. (24th March 2018) - Lamb, Iain R.; Novielli, Nicole M.; Murrant, Coral L.
Abstract : Key points: The current theory behind matching blood flow to metabolic demand of skeletal muscle suggests redundant interactions between metabolic vasodilators. Capillaries play an important role in blood flow control given their ability to respond to muscle contraction by causing conducted vasodilatation in upstream arterioles that control their perfusion. We sought to determine whether redundancies occur between vasodilators at the level of the capillary by stimulating the capillaries with muscle contraction and vasodilators relevant to muscle contraction. We identified redundancies between potassium and both adenosine and nitric oxide, between nitric oxide and potassium, and between adenosine and both potassium and nitric oxide. During muscle contraction, we demonstrate redundancies between potassium and nitric oxide as well as between potassium and adenosine. Our data show that redundancy is physiologically relevant and involved in the coordination of the vasodilator response during muscle contraction at the level of the capillaries. Abstract: We sought to determine if redundancy between vasodilators is physiologically relevant during active hyperaemia. As inhibitory interactions between vasodilators are indicative of redundancy, we tested whether vasodilators implicated in mediating active hyperaemia (potassium (K + ), adenosine (ADO) and nitric oxide (NO)) inhibit one another's vasodilatory effects through direct application of pharmacological agents and during muscle contraction. Using the hamster cremaster muscle and intravital microscopy, we locally stimulated capillaries with one vasodilator in the absence and the presence of a second vasodilator (10 −7 m S ‐nitroso‐ N ‐acetylpenicillamine (SNAP), 10 −7 m ADO, 10 mm KCl) applied sequentially and simultaneously, and observed the response in the associated upstream 4A arteriole controlling the perfusion of the stimulated capillary. We found that KCl significantly attenuated SNAP‐ and ADO‐induced vasodilatations by ∼49.7% and ∼128.0% respectively and ADO significantly attenuated KCl‐ and SNAP‐induced vasodilatations by ∼94.7% and ∼59.6%, respectively. NO significantly attenuated KCl vasodilatation by 93.8%. Further, during muscle contraction we found that inhibition of NO production usingl ‐ N G ‐nitroarginine methyl ester and inhibition of ADO receptors using xanthine amine congener was effective at inhibiting contraction‐induced vasodilatation but only in the presence of K + release channel inhibition. Thus, only when the inhibiting vasodilator K + was blocked was the second vasodilator, NO or ADO, able to produce effective vasodilatation. Therefore, we show that there are inhibitory interactions between specific vasodilators at the level of the capillary. Further, these inhibitions can be observed during muscle contraction indicating that redundancies between vasodilators are physiologically relevant and influence vasodilatation during active hyperaemia. Key points: The current theory behind matching blood flow to metabolic demand of skeletal muscle suggests redundant interactions between metabolic vasodilators. Capillaries play an important role in blood flow control given their ability to respond to muscle contraction by causing conducted vasodilatation in upstream arterioles that control their perfusion. We sought to determine whether redundancies occur between vasodilators at the level of the capillary by stimulating the capillaries with muscle contraction and vasodilators relevant to muscle contraction. We identified redundancies between potassium and both adenosine and nitric oxide, between nitric oxide and potassium, and between adenosine and both potassium and nitric oxide. During muscle contraction, we demonstrate redundancies between potassium and nitric oxide as well as between potassium and adenosine. Our data show that redundancy is physiologically relevant and involved in the coordination of the vasodilator response during muscle contraction at the level of the capillaries.